Gamification of the TPACK Model in Programming Education through Virtual Reality - Juan Salvador Hernández Valerio; Edith Olivo García; Reyna Moreno Beltrán (Universidad de Guadalajara, 2024)
In recent years, the combination of pedagogy and technology has revolutionized education, providing teachers with innovative tools to transform their work in the classroom. With the aim of transforming and improving the teaching of subjects related to technical and programming concepts, it was decided to develop a virtual reality (VR) tool to address the challenge of ensuring that students acquire, understand, and can effectively apply knowledge in practice through the TPACK model. The approach applied for this research was quantitative, supported by an applied experimental design and a convenience sample of 49 students from the Faculty of Informatics at the Autonomous University of Querétaro, Mexico. Likert scale surveys were conducted to measure the improvement and transformation of teaching through the virtual tool and the TPACK model. The results demonstrated that the strategy of using VR for teachers to provide students with a platform featuring game mechanics helps transform and improve learning. It was also concluded that one of the greatest strengths of this tool is that it removes the user from the traditional classroom, mitigating pressure or negative predisposition towards unknown or difficult-to-understand concepts.